Drugs and clinical trials in neurodegenerative diseases - Paolo Stanzione; Domenicantonio Tropepi (Istituto Superiore di Sanità, 2011)
Neurodegenerative diseases are disabling conditions continuously increasing due to aging of population. A disease modifying therapy that slows or stops disease progression is therefore a major unmet medical need. Unfortunately, research for effective treatments is hampered by lack of knowledge on the pathologic processes underpinning these diseases and of reliable biomarkers. Clinical trials are difficult, as they require large populations that need to be followed for very long periods to capture possible effects on disease progression. These difficulties produce frequent failures and waste of human and economic resources. Since research has to continue in this area, until comprehensive knowledge of basic pathologic processes is obtained, alternative study designs can be considered to identify disease modifiers and to reduce costs of clinical studies.